Private Vehicle Dependency In Pontianak City Through The Social Action Perspective - Dara Septika Natalia Anggraeni; Arkanudin; Sudirman; Herlan; Indah Listyaningrum (Jurnal Sosiologi Nusantara, 2025)
In Pontianak City, the increasing reliance on private vehicles has significantly contributed to traffic congestion, environmental pollution, and challenges in urban mobility, raising critical concerns about the declining use of public transportation options such as the oplets. This study investigates the underlying reasons for the preference for private vehicles among the residents of Pontianak and examines the resulting impacts of the shift from public to private transportation. Grounded in Max Weber's Social Action Theory, the research employs a qualitative method involving 14 purposively selected informants, with data analyzed using Miles and Huberman’s Interactive Model. The findings reveal that residents favor private vehicles due to a combination of internal factors—such as flexibility, comfort, time efficiency, convenience, economic considerations, safety, and travel purposes—and external factors, including inadequate public transportation infrastructure and weather conditions. These factors reflect how individual motives, rational choices, and situational influences shape transportation behavior. The shift has led to various impacts, including traffic congestion, air and noise pollution, higher accident risks, reduced social interaction, social stratification, and increasing individualism. The study concludes that enhancing the quality, accessibility, and attractiveness of public transportation is essential to reduce overdependence on private vehicles and promote more sustainable urban mobility in Pontianak.